High-throughput analysis revealed mutations' diverging effects on SMN1 exon 7 splicing - Souček, Přemysl; Réblová, Kamila; Kramárek, Michal; Radová, Lenka; Grymová, Tereza; Hujová, Pavla; Kováčová, Tatiana; Lexa, Matej; Grodecká, Lucie; Freiberger, Tomáš (RNA biology, 2019)
Splicing-affecting mutations can disrupt gene function by altering the transcript assembly. To ascertain splicing dysregulation principles, we modified a minigene assay for the parallel high-throughput evaluation of different mutations by next-generation sequencing. In our model system, all exonic and six intronic positions of the SMN1 gene's exon 7 were mutated to all possible nucleotide variants, which amounted to 180 unique single-nucleotide mutants and 470 double mutants. The mutations resulted in a wide range of splicing aberrations. Exonic splicing-affecting mutations resulted either in substantial exon skipping, supposedly driven by predicted exonic splicing silencer or cryptic donor splice site (5'ss) and de novo 5'ss strengthening and use. On the other hand, a single disruption of exonic splicing enhancer was not sufficient to cause major exon skipping, suggesting these elements can be substituted during exon recognition. While disrupting the acceptor splice site led only to exon skipping, some 5'ss mutations potentiated the use of three different cryptic 5'ss. Generally, single mutations supporting cryptic 5'ss use displayed better pre-mRNA/U1 snRNA duplex stability and increased splicing regulatory element strength across the original 5'ss. Analyzing double mutants supported the predominating splicing regulatory elements' effect, but U1 snRNA binding could contribute to the global balance of splicing isoforms. Based on these findings, we suggest that creating a new splicing enhancer across the mutated 5'ss can be one of the main factors driving cryptic 5'ss use.
Keywords: mutace; Molecular Dynamics Simulation; buněčné linie; mutageneze; High-Throughput Nucleotide Sequencing; vazba proteinů; RNA malá jaderná; protein přežití motorických neuronů 1; lidé; simulace molekulární dynamiky; Nucleic Acid Conformation; Survival of Motor Neuron 1 Protein; Mutation; RNA, Small Nuclear; Cell Line; konformace nukleové kyseliny; RNA Splice Sites; Computational Biology; Exons; vysoce účinné nukleotidové sekvenování; Mutagenesis; alternativní sestřih; exony; Alternative Splicing; místa sestřihu RNA; výpočetní biologie; Protein Binding; Humans